Pengaruh Karakter Religius Terhadap Perilaku Seksual Siswa Kelas 6 SD Islam Al-Bayan Wiradesa Pekalongan - Aristiyanto, Roma; Indrawati, Triana (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
In today's era dating is a common thing among primary schoolstudent. The occurrence of this dating trend causes things that have a negative impact. This sexual behavior can occur because of the lack of self-limiting such as the low religiouscharacter of students. This article is intended to investigate the effect of religious character on sexual behavior of elementary school students. This type of research is a field research using a quantitative approach and taking the subject of studentsclass 6 SD Islam Al-Bayan Wiradesa Pekalongan. There is a population of class 6 (6A and 6B) totaling 47 students, the entire population is used as a sample (total sampling). The data were collected using a Likert scale questionnaire statement. The results of the data are processed through statistical calculations from preliminary analysis, prerequisite tests, and hypothesis testing using SPSS V.26. The data obtained from the students' religious character is very high at 107.87, sexual behavior is very low at30.38, and there is a significant negative influence between religious characters on sexual behavior by 95.4%.